Mathematical Engagement In Interactive Learning: A Case Study Of The Use Of Lumio In Understanding The Concept Of Normal Distribution - Lestari, Indri; Hadi, Windia; Giyanti, Giyanti; Khotimah, Khotimah (Program Studi Tadris Matematika dan Tadris Ilmu Pengetahuan Alam, Fakultas Tarbiyah dan Ilmu Keguruan (FTIK), Universitas Islam Negeri (UIN) Datokarama Palu, 2025)
Understanding the concept of normal distribution in statistics is often challenging for students, as it requires a deep understanding of symmetry, probability distribution, and the use of normal distribution tables. These challenges are often caused by difficulties in connecting theoretical concepts with data visualization and in comprehending z-score transformations. This study aims to analyze students' mathematical engagement in understanding the concept of normal distribution using Lumio-based interactive media. The study employed a quantitative, quasi-experimental design, with a pre-test post-test control group design. The experimental group engaged in learning using Lumio-based interactive media, while the control group received traditional lecture-based teaching methods. The research instruments included a concept comprehension test, a mathematical engagement questionnaire, and an analysis of Lumio activity logs. The data were analyzed using paired sample t-tests and ANCOVA to evaluate the effectiveness of Lumio in improving students' mathematical engagement and conceptual understanding. The results showed a significant difference between pre-test and post-test scores in both the experimental and control groups. The experimental group, which used Lumio, showed a significantly higher improvement in both conceptual understanding and engagement compared to the control group. The findings suggest that using Lumio-based learning significantly enhanced students' engagement and understanding of normal distribution, compared to the conventional teaching methods